Intramedulární hřeb v léčbě metastatického postižení diafýz dlouhých kostí: retrospektivní studie s ohledem na srovnání prognózy doby dožití a reálné přežití pacientů - Valoušek, Tomáš; Pazourek, Lukáš; Tomáš, Tomáš; Mahdal, Michal; Janíček, Pavel; Apostolopoulos, Vasileios (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
PURPOSE OF THE STUDY The paper focuses on the potential use of nail osteosynthesis in diaphyseal metastases of long bones. The purpose of the paper is to assess the outcomes of intramedullary osteosynthesis in pathologic and impending pathologic fractures, to evaluate patient survival and potential complications. MATERIAL AND METHODS The retrospective study evaluated a cohort of 42 patients (19 men and 23 women) in whom intramedullary osteosynthesis was performed for complete pathologic fracture (28 patients) or impending pathologic fracture (14 patients) between 2010 and 2019. Of the total number of 42 patients, 31 patients' lower limbs were affected, namely by 17 pathologic fractures and 14 impending fractures. There were 11 humerus fractures. The mean age was 61.8 years (range 41-84 years). In the followed-up cohort, the patient survival after osteosynthesis with intramedullary nails, complications occurred and post-operative mobility of the patient were assessed. The functional outcomes were evaluated using the Musculoskeletal Tumor Society (MSTS) scoring system. The unpaired Mann-Whitney test was used to test the significance of the difference in functional outcomes and survival between the followed-up groups. Survival longer than 6 months was evaluated using Fisher's exact test. The level of statistical significance used for the test was p 0.05. RESULTS The investigated indicator was patient survival, which was 11.3 months (range 1-50 months) on average. In the group of impending fractures, the mean survival was 13.5 months. In the group of pathologic fractures, the survival was 10 months. The functional outcome in 16 followed-up patients at three months after intramedullary osteosynthesis according to the MSTS score was 46.9% (30-66.7%). At the level of significance of p 0.05, the statistically significant difference in the functional outcomes between the group with preventive intramedullary osteosynthesis and the group with nail osteosynthesis of the pathologic fracture was not confirmed (p=0.952). When comparing the patient survival after nail osteosynthesis with impending pathologic fracture and the survival of patients with pathologic fracture, a statistically significant difference in survival between these two groups (p=0.520) was not confirmed. The patient survival of longer than 6 months was 71% in the group of impending fractures and 40% in the group of pathologic fractures. DISCUSSION The occurrence of pathologic fracture is associated with increased pain, loss of function, and according to some authors, a higher risk of death. Surgical treatment options include intramedullary osteosynthesis, plate osteosynthesis with cement filling, implantation of an intercalary spacer, and implantation of tumor endoprostheses. When deciding on a surgical procedure, an account is taken of the expected survival of the patient. In patients with an expected survival of up to 6 months, intramedullary osteosynthesis is indicated as a palliative surgical intervention. The most common complications include implant failure and metastatic progression. CONCLUSIONS Intramedullary osteosynthesis is the method of choice in treating pathologic fractures or impending pathologic diaphyseal fractures of long bones in patients with an expected predicted survival of up to 6 months. Intramedullary osteosynthesis aims to reduce pain and enable early verticalization. The study confirmed the importance of preventive intramedullary osteosynthesis and its effect on survival compared to the survival of patients with a pathologic fracture. Key words: skeletal metastases, diaphyseal metastases, intramedullary osteosynthesis, pathologic fracture, impending fracture.
Keywords: výsledek terapie; intramedulární fixace fraktury; Male; retrospektivní studie; Neoplasms; kostní hřeby; Fractures, Spontaneous; Fracture Fixation, Intramedullary; Adult; fraktury spontánní; Aged; dospělí; mužské pohlaví; senioři; fraktury humeru; Treatment Outcome; senioři nad 80 let; Humeral Fractures; lidé; ženské pohlaví; Humans; Bone Nails; Aged, 80 and over; nádory; Retrospective Studies; Female; lidé středního věku; Middle Aged